Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbagen.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Protection against fine particle-induced pulmonary and systemic inflammation by omega-3 polyunsaturated fatty acids

Abstract: Our findings demonstrate that elevating tissue omega-3 levels can prevent and treat fine particle-induced health problems and thereby present an immediate, practical solution for reducing the disease burden of air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…Using this model, we found in this experiment that PM 2.5 exposure for 12 weeks aggravates ICA in a manner that appears to involve the induction of systemic inflammation and oxidative stress. Additionally, we found that omega‐3 fatty acid (O3FA) dietary supplementation, which has been shown elsewhere to be capable of ameliorating fine particle‐induced systemic inflammation, prevents ICA development . This lends further credence to our hypothesis that an inflammatory mechanism is involved in the pathogenic effect exerted by PM 2.5 on the cerebral vasculature.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Using this model, we found in this experiment that PM 2.5 exposure for 12 weeks aggravates ICA in a manner that appears to involve the induction of systemic inflammation and oxidative stress. Additionally, we found that omega‐3 fatty acid (O3FA) dietary supplementation, which has been shown elsewhere to be capable of ameliorating fine particle‐induced systemic inflammation, prevents ICA development . This lends further credence to our hypothesis that an inflammatory mechanism is involved in the pathogenic effect exerted by PM 2.5 on the cerebral vasculature.…”
Section: Introductionsupporting
confidence: 65%
“…Studies of Mediterranean populations showed that regular consumption of dietary O3FA is associated with a lower incidence of cardiovascular disease; findings from these studies suggest that the anti‐atherogenic effects of O3FA are exerted in multiple ways, including modulation of the arterial initial uptake and binding of LDL, inhibition of recruitment of and pro‐inflammatory mediator production by leukocytes, and diminution of inflammatory and oxidative stress in vascular cells . More recently, elevated tissue O3FA levels, whether achieved before or after exposure, have also been shown to suppress the pulmonary and systemic inflammation induced by fine particle inhalation, which is consistent with our results . In addition to supporting the current evidence base regarding the anti‐atherogenic properties of O3FA, however, our results also expand it, as the vast majority of studies attempting to elucidate O3FA's mechanistic effects on atherosclerosis have focused exclusively on the extracranial vasculature …”
Section: Discussionmentioning
confidence: 99%
“…11 and 12). UFPs can penetrate deep into the lung, can be transported into the bloodstream, and can translocate to different organs (Li et al, 2017b;Oberdörster et al, 2004). The upper left plot shows an urban aerosol number PSD with lognormal fitting parameters listed.…”
Section: Urban Aerosol Psds: Implications For Indoor Air Quality and Aementioning
confidence: 99%
“…This is important when considering the observed increase in air pollution in many overpopulated parts of the world and the link to risks of pulmonary and peripheral diseases. In fact, biological and epidemiological evidence suggest that exposure to PM and related components of air pollution can contribute to oxidative stress and inflammation, suggesting that intake of diets enriched in antioxidant and anti‐inflammatory nutrients should be advised to downregulate pulmonary disease risks . There is evidence that specific nutrients can actually reduce the toxicity and health complications associated with pollutant exposure.…”
Section: Influence Of Nutrition On Pollutant Toxicitymentioning
confidence: 99%
“…In fact, biological and epidemiological evidence suggest that exposure to PM and related components of air pollution can contribute to oxidative stress and inflammation, suggesting that intake of diets enriched in antioxidant and anti-inflammatory nutrients should be advised to downregulate pulmonary disease risks. [57][58][59] There is evidence that specific nutrients can actually reduce the toxicity and health complications associated with pollutant exposure. Diets rich in bioactive food components, such as omega-3 fatty acids and polyphenols, contain high levels of antioxidant and anti-inflammatory compounds that are capable of blunting the toxic and inflammatory effects of pollutant exposure.…”
Section: Influence Of Nutrition On Pollutant Toxicitymentioning
confidence: 99%